Glacier Runoff Variation Since 1981 in the Upper Naryn River Catchments, Central Tien Shan - Saks, Tomas; Pohl, Eric; Machguth, Horst; Dehecq, Amaury; Barandun, Martina; Kenzhebaev, Ruslan; Kalashnikova, Olga; Hoelzle, Martin (Frontiers in Environmental Science, 2022)
Water resources in Central Asia strongly depend on glaciers, which in turn adjust their size in response to climate variations. We investigate glacier runoff in the period 1981–2019 in the upper Naryn basin, Kyrgyzstan. The basins contain more than 1000 glaciers, which cover a total area of 776 km$^{2}$. We model the mass balance and runoff contribution of all glaciers with a simplified energy balance melt model and distributed accumulation model driven by ERA5 LAND re-analysis data for the time period of 1981 - 2019. The results are evaluated against discharge records, satellite-derived snow cover, stake readings from individual glaciers, and geodetic mass balances. Modelled glacier volume decreased by approximately 6.7 km$^{3}$ or 14%, and the majority of the mass loss took place from 1996 until 2019. The decreasing trend is the result of increasingly negative summer mass balances whereas winter mass balances show no substantial trend. Analysis of the discharge data suggests an increasing runoff for the past two decades, which is, however only partly reflected in an increase of glacier melt. Moreover, the strongest increase in discharge is observed in winter, suggesting either a prolonged melting period and/or increased groundwater discharge. The average runoff from the glacierized areas in summer months (June to August) constitutes approximately 23% of the total contributions to the basin's runoff. The results highlight the strong regional variability in glacier-climate interactions in Central Asia.